Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$P(X_0 = j, X_m \ne j, 1 \le m \le n-1) = P(X_m \ne j, 1 \le m \le n-1) - P(X_m \ne j, 0 \le m \le n-1) $


$\{X_n\}$ is an irreducible Markov Chain with a finite state space.

share|cite|improve this question
up vote 3 down vote accepted

This is basic probability; it has nothing to do with Markov chains. Define $A=(X_0=j)$ and $B=\cap_{m=1}^{n-1}(X_m\neq j)$. Then your equation simply says $$\mathbb{P}(A\cap B)=\mathbb{P}(B)-\mathbb{P}(\bar A\cap B).$$ This is true because $B$ is the disjoint union of $A\cap B$ and $\bar A\cap B$, where I'm using $\bar A$ to denote the complement of $A$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.